ASSESSMENT OF HIP JOINT ENDOPROSTHESIS TREATMENT EFFECTIVENESS AND ITS IMPACT ON PATIENTS' QUALITY OF LIFE - Y.U., Joynarov; N.R, Ishburiev; U.M, Shermatov; Z.Sh, Abulfayzov; M.O, Djuraev (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study investigates the effectiveness of total hip arthroplasty (THA) in restoring joint function and enhancing the overall quality of life for patients with severe hip joint disorders. Method: Conducted at the Department of Traumatology and Orthopaedics, Surkhandarya Regional Multidisciplinary Medical Centre, Uzbekistan, the study observed 82 patients who underwent THA between 2022 and 2024. The Harris Hip Score and SF-36 health survey were used to evaluate patients’ physical function, pain levels, emotional state, and social well-being before surgery and at 3 and 12 months postoperatively. Results: Findings demonstrated a significant reduction in pain and substantial improvements in mobility, independence, and physical health indicators. Patients also reported enhanced mood, sleep quality, and life satisfaction, suggesting broad psychosocial benefits beyond physical rehabilitation. Novelty: Unlike prior studies focused solely on biomechanical outcomes, this research emphasizes the holistic impact of hip endoprosthesis, highlighting THA as not merely a mechanical intervention but a transformative procedure with profound implications for psychological well-being and quality of life. The study advocates for patient-centered orthopaedic care with integrated postoperative support.